2017
DOI: 10.1080/14786419.2017.1399380
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of borneol esters and their antimicrobial activity

Abstract: Seventeen borneol esters (1-17) were synthesised by conventional and microwave-assisted methodology using DIC/DMAP, and seven are described for the first time (8, 9, 10, 12, 13, 16 and 17). The microwave-assisted methodology was carried out without use of solvents, displayed short reaction times, and showed equal or higher yields for all the long-chain esters and three aromatic compounds (11, 12 and 14) when compared to the conventional approach. All the borneol esters were evaluated against the bacteria Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Borneol, including natural borneol (D-borneol) and synthetic borneol (Borneol, isoborneol, and camphor) ( Chinese Pharmacopoeia Commission, 2020 ), has been used in TCM clinical applications for more than 2,000 years ( Wang et al, 2017 ). Our previous study showed that the MIC of borneol against sensitive or FLC-resistant C. albicans was >1.28 mg/mL, which was similar to the previous report ( E Silva et al, 2018 ). The MIC of KBN against C. albicans was 6.25 mg/mL, and the concentration of borneol in it was only 0.03 mg/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Borneol, including natural borneol (D-borneol) and synthetic borneol (Borneol, isoborneol, and camphor) ( Chinese Pharmacopoeia Commission, 2020 ), has been used in TCM clinical applications for more than 2,000 years ( Wang et al, 2017 ). Our previous study showed that the MIC of borneol against sensitive or FLC-resistant C. albicans was >1.28 mg/mL, which was similar to the previous report ( E Silva et al, 2018 ). The MIC of KBN against C. albicans was 6.25 mg/mL, and the concentration of borneol in it was only 0.03 mg/mL.…”
Section: Discussionsupporting
confidence: 90%
“…The most active compounds (–)-bornyl p-coumarate ( 6 ) and (–)-bornyl cis-4-hydroxycinnamate ( 7 ) showed good activity against S. aureus and MRSA, with MIC values of 2–8 µg/mL. Similar structures exhibiting potent antibacterial activity were reported in previous studies, such as bornyl caffeate, bornyl coumarate [ 24 ], bornyl 3′, 4′-dimethoxybenzoate and bornyl 3′, 4′, 5′-tri-methoxybenzoate [ 25 ]. The antibacterial activity of compound 7 was slightly weaker than that of compound 6 , which may be attributed to the different configuration of double bonds in their structures.…”
Section: Discussionsupporting
confidence: 54%
“…The particular biological properties of (–)-borneol derivatives belonging to the ester compounds significantly affect their applicability in medical areas, especially for diverse therapeutic fields [ 104 , 107 , 108 , 109 ]. (–)-Borneol esters are also found in a few plant families: For instance, the hydroxycinnamic variety in Eupatorium deltoideum Poepp.…”
Section: Monoterpene Bicyclic Derivativesmentioning
confidence: 99%
“…A large set of monoterpene derivatives that belong to the group of (–)-borneol esters were designed, synthesized, and examined with a view to their antimicrobial activity [ 109 ]. Desired compounds were prepared by the conventional and microwave-assisted methodology and the obtained (–)-borneol derivatives contained various aliphatic and aromatic moieties ( Figure 34 ); all of them ( 130 ) were tested for their antibacterial and antifungal properties.…”
Section: Monoterpene Bicyclic Derivativesmentioning
confidence: 99%
See 1 more Smart Citation